THE IMPORTANCE OF PLANTS AND THEIR MEDICINAL PROPERTIES IN THE ANDEAN WORLD - Rogger Silva; María del Rosario Vivar (Colegio de Médicos del Azuay, 2024)
The present bibliographic review gathers essential information about medicinal plants and their contribution to improve people´s health and welfare. Since the past, when people used to dedicate their lives to agriculture and farming, plants have been essential part of their growing and development, since ancient people really trusted in their benefits and took advantage of the medicinal properties that plants have and contribute to improve people´s quality of live. In this sense, the present study aims to highlight the importance, medicinal properties and benefits that plants provide to people, not only in the Andean region but in Ecuador. The research methodology involves a multidisciplinary approach, which includes biological, botanic and socio cultural perspective. The main result indicates that even though researches have dedicated to investigate about medicinal plants, there is some lack of updated information that permits to identify specific plants and their scientific benefits in particular cases.